A Single Phase Single Stage Fault Tolerant Hybrid 5-L Inverter for Photo Voltaic System Applications - et. al, M.Venkateswarlu (International Journal of Advanced Science and Technology, 2020)
Abstract: Multi level converters are highly attracted in PV Systems applications due to its less voltage stresses, less THD and high efficiency. This paper presents a fault tolerant single phase hybrid 5-L converter, in which a combination of 3-Level multilevel inverter and half bridge inverter used for generation of 5 levels voltage waveform. This converter is capable of fault tolerant for open and short circuit faults. In normal operating conditions the output of the converter is at 5 levels and during the fault conditions it turns into 3 levels output voltage. The harmonic distortion in output AC current is less than 10% in both normal and fault conditions. The conversion capability and the ease of operation, show the effectiveness of the converter. The proposed converter is validated under fault tolerant operation and simulated by using MATLAB/SIMULINK.